The physical impact of migraines on female chiropractic patients: A qualitative study - Ashalya Pirthiraj; Raisuyah Bhagwan (AOSIS, 2023)
Background: Migraines are highly prevalent among the female population and have a significant burden on one's quality of life and physical functioning. Aim: The study explored the physical impact and contributory factors of migraines on women and their experience of chiropractic treatment for migraine pain management. Setting: The study was conducted in the eThekwini region of KwaZulu-Natal, South Africa. Methods: The study used a qualitative descriptive design and adopted purposive sampling. The data were collected through 12 semi-structured interviews, between March and September 2021, and analysed using thematic analysis. Results: The first theme that emerged focused on the physical effects of migraines. The second theme related to the factors that contributed to migraines. The third theme that emerged focused on chiropractic treatment for migraines. Conclusion: The majority of the participants experienced chronic migraines and migraines without aura. The participants felt incapacitated and experienced debilitating physical effects with their migraines. The study highlighted that chiropractic treatment was favourable among the female population in improving the quality of life and reducing the severity, disability, duration of suffering and frequency of migraines. It was revealed that chiropractic was the preferred non-pharmacological approach for migraine treatment, as it proved to be a beneficial and effective treatment for migraine pain management. Contribution: The findings contribute to a greater awareness of chiropractic as an effective evidence-based treatment approach for migraine pain management, which may be beneficial to migraineurs and healthcare practitioners.